VIBRATION MEASUREMENT METHOD OF WIND TURBINE BLADE BASED ON BINOCULAR PHOTOGRAM METRY - YAKUP AhMat; WANG WenYun; GULBAHAR TohTi; SUN Zhi; MAMTIMIN GeNi (Jixie qiangdu)
binocular photogrammetry vibration measurement method for considering the radial and tangential distortion parameters calibration by using the Levenberg-Marquardt algorithm based nonlinear optimization was proposed. As an example,the modal frequency identified of a wind turbine blade. The vibration images sequence of the blade was acquired synchronously by two cameras and the target was segmented by adaptive binary dynamic threshold method,the direction with fastest grayscale gradient of the coding point as the edge,the circle curve was fitted by the least squares and iterative method,and the precise suppixel central coordinates of the coding point in the dynamic consecutive images were obtained by the gray square centroid method.Each coding point is similar to a small "displacement transducer"that reflects the blade’s time domain vibration response.Finally,the blade’s natural modal frequency was obtained from the time domains response,and compared with the results of the finite element and Laser Doppler Vibrometry,the relative error of vibration frequencies less than 5%,which verified the reliability and effectiveness of binocular photogrammetry method.